(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article presents the results of a study conducted among cadets at the Military Institute (Military Engineering Institute of radio Electronics and Communications), which assessed the development of two important professional qualities: stress resilience and determination. Their readiness for professional work was also assessed, as well as the impact of educational services at military educational institutions on the development of professionally important qualities.